Al-Ghazzali's Contributions to Sufism: A Comprehensive Analysis of His Spiritual Philosophy and Ethical Framework - K M A Ahamed Zubair (Indonesian Journal of Research in Islamic Studies, 2026)
Background: Imam Al-Ghazzali (1058–1111 CE), known as "Hujjat al-Islam" (The Proof of Islam), emerged during an era of intense intellectual conflict between rationalist philosophy and religious faith. Despite his profound influence on Islamic thought, a comprehensive analysis of his integrated spiritual and ethical framework remains limited in contemporary scholarship. Objectives: This study examines Imam Al-Ghazzali's contributions to Sufism, analyzing his epistemological framework for spiritual knowledge, his ethical constitution rooted in Sufi psychology, his critique of philosophy, and his integration of Sharia compliance with spiritual purification. Methods: A qualitative historical-analytical research design was employed, utilizing content analysis of primary sources, including Al-Ghazzali's autobiographical Deliverance from Error, his magnum opus The Revival of the Religious Sciences, The Criterion of Action, and The Incoherence of the Philosophers. Results: The findings reveal that Al-Ghazzali established spiritual unveiling (kashf) as a valid source of certainty alongside reason and revelation, developed a comprehensive ethical framework based on refining the psychological powers of reason, desire, and anger, and demonstrated that authentic Sufism requires strict adherence to Islamic law. Conclusion: Al-Ghazzali's synthesis created an enduring framework uniting intellectual rigor with heartfelt devotion, offering a balanced approach to faith that continues to influence Islamic spirituality and ethics. Contributions: This research contributes to Islamic studies scholarship by providing a systematic analysis of Al-Ghazzali's integrated vision of Sufism and its contemporary relevance for discussions on reason, spirituality, and spiritual formation.